Implementasi Program Keluarga Harapan Kecamatan Cisitu Kabupaten Sumedang - Rika Kusdinar; Dewi Inggit Pergiwa (PERSPEKTIF, 2021)
The purpose of the research that researchers do is to find out the extent of the Implementation of the Family Hope Program in Cisitu District of Sumedang Regency. The method used in this study is a qualitative research method which is used in research based on the philosophy of postpositivism, used to examine the natural conditions of objects, where researchers act as key instruments, data collection techniques are carried out by triangulation (combined), data analysis is inductive, and qualitative research results emphasize more meaning than generalization. The technique used in taking samples is to use purposive sampling, which is sampling based on needs, so the samples in this study were 4 people. As for what is determined to be the informant in this study are the executors who are considered to have authority, information, and are involved in implementation of the Family Hope Program in Cisitu District of Sumedang Regency. Based on the results of the study, the researchers can describe that the Implementation of the Family Hope Program in Cisitu District of Sumedang Regency can be side to be quite well run according to the success factor of the implementation. But on the other hand there are problems related to facilities, both facilities and infrastructure provided are not yet fully adequate, there are still many shortcomings, this is because the government and the organizers only provide basic facilities.